Women's Participation in PON XX Papua - Aryani, Mela (Universitas Suryakancana, 2022)
In sport, women and men have the same position, opportunities and rights, but in reality women are still underestimated. the participation of women as athletes, coaches, officials and in the organizational structure of sports still tends to be less than that of men. The purpose of this study was to see the extent of women's participation in the XX Papua PON event. The method used in this study is a descriptive method with a quantitative approach. The results of this study are that of the 7,046 athletes who competed in the Papua PON event, only 2,886 (40.1%) were female athletes, while the remaining 4,160 (49.9) were male athletes. There are various factors that cause the participation rate of women to be less than that of men, including that sport is still considered something exclusive and only dominated by men and sport is still considered something masculine. In addition, there is a tendency that men consider women as weak creatures so that they must be protected and do not deserve to play a role in determining sports decisions.Keywords: Gender, Women, PON XX Papua